Pengaruh Disiplin Kerja, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT PLN (Persero) Rayon Kuta - Apliana Kaka (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the influence of work discipline, work motivation, and work environment on employee performance at PT. PLN (Persero) Rayon Kuta by involving all employees as the research population. The approach used is quantitative with data collection through distributing questionnaires to respondents. The number of respondents was 100 people determined using a saturated sampling technique, namely the entire population was sampled because it was considered to meet the appropriate criteria, namely active employees of PT. PLN (Persero) Rayon Kuta. The data obtained were then analyzed using linear regression, with a t-test to test the partial effect of each variable and an F-test to determine the simultaneous effect. The results of the t-test indicate that work discipline, work motivation, and work environment individually have a positive and significant effect on employee performance, meaning that the better the level of discipline, the higher the motivation, and the more conducive the work environment, the more optimal the employee performance produced. Meanwhile, the results of the F-test show that the three variables simultaneously also have a significant effect on employee performance. Thus, this study confirms that the factors of work discipline, work motivation, and work environment have an important role in increasing productivity, work quality, and the achievement of company goals. Therefore, companies need to pay attention to these three aspects continuously to maintain and improve employee performance in the future.